New records of two species of the coral reef shrimp genus Thor Kingsley, 1878 (Crustacea: Decapoda: Thoridae) from the Ryukyu Islands, Japan - Komai, Tomoyuki; Okuno, Junji; Minemizu, Ryo (Zootaxa, 2015)
The caridean shrimp genus Thor Kingsley, 1878 (Thoridae) is currently represented by 14 species distributed in shallow tropical to subtropical waters in the Indo-Pacific, East Pacific and West Atlantic oceans. In this study, two species of the genus are reported on the basis of material from Okinawa and Kume islands in the Ryukyu Archipelago, southern Japan. Thor leptochelus (Xu & Li, 2015) n. comb., recently described from Xisha Islands, China and originally assigned to Thinora Bruce, 1997, is transferred to Thor. Relationship of the species to three congeneric species (T. cordelli Wicksten, 1996, T. spinipes Bruce, 1983 and T. spinosus Boone, 1935) is discussed. The second is T. marguitae Bruce, 1973, representing the rediscovery since the original description and new record for Japanese waters. The four specimens of T. leptochelus were all free-living, whereas the single specimen of T. marguitae was found to be associated with a solitary fungiid coral, as previously reported.